Meningocele in a Congolese Female with Beckwith-Wiedemann Phenotype. (25th December 2014) - Mbuyi-Musanzayi, Sébastien; Lubala Kasole, Toni; Lumaka, Aimé; Kayembe Kitenge, Tony; Kabamba Ngombe, Leon; Kalenga Muenze, Prosper; Lukusa Tshilobo, Prosper; Tshilombo Katombe, François; Banza Lubaba Nkulu, Célestin; Devriendt, Koenraad
Abstract : Beckwith-Wiedemann syndrome (BWS) is a rare congenital syndrome characterized by an overgrowth, macroglossia, exomphalos, and predisposition to embryonal tumors. Central nervous abnormalities associated with BWS are rare. We describe a one-day-old Congolese female who presented meningocele associated with BWS phenotype.